AAO/NANOS clinical neuro-ophthalmology image collection for ophthalmic practitioners (San Francisco : American Academy Opthalmology, 1999)
More than 400 captioned clinical images of common and uncommon and rarely photographed neuro-ophthalmic conditions; includes 155 case summaries. All images are downloadable.
Title from disc label
Larry P. Frohman, Andrew G. Lee.
System requirements: Computer using pentium 100 MHz processor or better; 32MB RAM; 4X-speed CD-ROM drive or better (2X-speed);640 x 480 monitor displaying 16-bit color; Microsoft Windows 95 or NT; Mouse or comparible pointing device
System requirements: Macintosh MHz 68030 (68040 or Power PC recommended); 8 MB of RAM (16 MB Power PC); 4X-speed CD-ROM drive or better (2X-speed minimum) ; System 7.01 or higher; double-speed CD-ROM drive
Keywords: Eye Diseases; Neulogic Manifestations